Protective effect of antioxidant enzymes against drug cytotoxicity in MCF-7 cells - Ozkan, A.; Fiskin, K. (Experimental Oncology, 2006)
Aim: To evaluate protective effect of antioxidant enzymes against epirubicin-HCI (EPI) cytotoxicity in vitro. Materials and Methods: Viability of MCF-7 cells treated with EPI was measured using the MTT test. Glutathione (GSH), protein content and enzymatic activity were measured spectrophotometrically. NADPH — dependent cytochrome P-450 reductase (NADPH-CYP-450) and glutathione S-transferase pi (GST-pi) expression in MCF-7 cells were determined by Western blot analysis. Results: The IC50 values of EPI in MCF-7 cells were 1.0, 0.7 and 0.5 ng/ml respectively for 24, 48 and 72 h applications. Simultaneously enzymatic activity of glutathione S-transferase, glutathione peroxidase, GSH and expression of GST-pi, NADPH-CYP-450 reductase were increased in EPI (1 ng/ml) — treated cells at the end of the 24 h incubation. Addition of superoxide dismutase, catalase and GSH decreased cytotoxicity of EPI. Conclusion: We hypothesized that the production of reactive oxygen species and hydrogen peroxide as result of EPI treatment can cause cytotoxicity in MCF-7 cells and antioxidant enzymes protect the cells against this process.